Who will go the extra mile? Selecting organizational citizens with a personality-based structured job interview - Heimann, Anna Luca; Ingold, Pia V.; Debus, Maike; Kleinmann, Martin (Journal of Business and Psychology, 2020)
Employees’ organizational citizenship behaviors (OCB) are important drivers of organizational effectiveness. Yet, there exist no established tools for selecting employees with a propensity to engage in OCB. Given that personality traits describe typical behavioral tendencies and are established OCB predictors, we propose that personality assessment is a useful approach for selecting employees who are likely to exhibit OCB. To test this proposition, we developed a structured job interview measuring the Big Five traits and then compared this interview to a personality self-report measure to determine which method of personality assessment works best for selecting organizational citizens. Employees (N = 223) from various occupations participated in the structured job interview and completed the personality self-report in a simulated selection setting. We then obtained supervisor ratings of employees’ OCB. Results supported the assumption that structured job interviews can be specifically designed to assess the Big Five personality traits and, most importantly, to predict OCB. Interview ratings of specific personality traits differentially predicted different types of OCB (i.e., OCB-compliance, OCB-helping, and OCB-initiative) and explained incremental variance in OCB over and above personality self-reports and verbal cognitive ability. Taken together, these findings expand our knowledge about dispositional predictors of OCBs, personality assessment in selection, and the design of job interviews.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Organizational citizenship behavior; Personality traits; Personnel selection; Structured interviews